The promoter -1031(T/C) polymorphism in tumor necrosis factor-alpha associated with polycystic ovary syndrome - Shin Joong-Sik; Lee Kyung-Ju; Choi Jin-Woo; Yun Ji-Hyun; Baek Kwang-Hyun (BMC, 2011)
Abstract Background A tumor necrosis factor-alpha is a multifunctional pro-inflammation cytokine, which has been considered as one of pathogenic factors for various diseases. The promoter -1031(T/C) polymorphism in the tumor necrosis factor-alpha gene was reported that it plays a part in reproduction-related diseases. Among these, polycystic ovary syndrome (PCOS) is known to be a common gynecological disease of women in reproductive age women. Here, we performed a comparative study of -1031(T/C) polymorphism of TNF-alpha gene with PCOS in a Korean population. Methods The -1031(T/C) polymorphism of TNF-alpha gene was analyzed by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) in a total of 217 PCOS patients and 144 matched female controls of healthy women. And statistical analysis was performed using HapAnalyzer. X2 test and logistic regression were utilized analyze the association between two groups. A p-value under 0.05 was considered statistically significant. Results The genotype and allelic frequencies were in Hardy-Weinberg equilibrium (HWE). There was strong association between the -1031(T/C) polymorphism in the promoter region of TNF-alpha gene and PCOS (p-value = 0.0003, odd ratio (OR) = 2.53). In addition, the frequency of C allele was significantly higher in PCOS patients compared with controls. Sequence analyses also showed the -1031(T/C) polymorphism of TNF-alpha gene. Conclusion This is the first study on the -1031(T/C) polymorphism of TNF-alpha gene in PCOS. We concluded that the -1031(T/C) polymorphism of TNF-alpha gene is associated with PCOS in a Korean population. Therefore, it is possible that it may be considered as a clinical biomarker to diagnose for PCOS, and is helpful in understanding the etiology for the pathogenesis of PCOS.